MODELO DE SISTEMA DE GESTÃO E COORDENAÇÃO DE PROJETOS PARA EMPRESAS CONSTRUTORAS E INCORPORADORAS - MANSO, Marco Antonio; MITIDIERI FILHO, Cláudio Vicente (Gestão & Tecnologia de Projetos, 2007)
This paper presents a model of design management and coordination system, oriented towards construction and real estate companies, that has as objective to contribute for the search of “operational excellence of the company” throughout the quality improvement of the design process. Some concepts, which are not always properly used by the majority of the design coordinators, are adopted, such as the knowledge management, risk analysis, communication management, among others, that, if used in a proper way, can contribute for the company success reaching. The model was developed from the premise that the design coordinator must be the main facilitator in the process, integrating the several other actors, since the decision to start the project until the post-occupation evaluation, using all the available tools, mainly the knowledge management, and having his action guided by the strategic plan of the company. For accomplishment of the research work it was adopted the case study method, having been elaborated a “preliminary model of design management system”, which was applied in the company where the author acts and later improved through case studies carried out involving seven construction and real estate companies in the São Paulo market. Key-words: coordination, management, quality, building design